Enhancer remodeling regulates epigenetic adaptation and resistance to MEK1/2 inhibition in triple-negative breast cancer. (2nd November 2017) - Bevill, Samantha M.; Zawistowski, Jon S.; Johnson, Gary L.
ABSTRACT: Kinase inhibitors targeting the mitogen/extracellular signal-regulated kinase kinase (MEK)- extracellular signal related kinase (ERK) signaling pathway have limited durability in inhibiting growth of triple-negative breast cancer. We defined genome wide enhancer remodeling following MEK inhibition capable of driving adaptive gene transcription. Targeting positive elongation factor (P-TEFb) transcriptional regulatory complex members can block enhancer remodeling making the response to MEK-ERK inhibition durable.